Synergy of Zakat and Waqf in Realizing Contemporary Sharia Economic Welfare: Analysis of Fiqh Muamalah - Al Kahfi; Muhamad Zen (al-Afkar, Journal For Islamic Studies, 2024)
This study analyzes the synergy between zakat and waqf in an effort to realize sharia economic welfare in the era with a contemporary approach to fiqh muamalah. Zakat and waqf are seen as important economic instruments in supporting fair distribution of wealth, poverty alleviation, and sustainable development in society. Through a literature study, this study found that the synergy between zakat which functions as direct redistribution and long-term waqf can strengthen the foundation of the people's economy. This study also discusses the challenges of regulation, professionalism of management, and low public literacy regarding the importance of zakat and productive waqf as economic tools. Recommendations in the form of implementing digital technology, improving amil governance, and cross-institutional collaboration are expected to optimize the role of zakat and waqf in creating a more just and economically prosperous society in accordance with the principles of fiqh muamalah.